Designing refractive index fluids using the Kramers–Kronig relations. (29th July 2020) - Sai, Tianqi; Saba, Matthias; Dufresne, Eric R.; Steiner, Ullrich; Wilts, Bodo D.
Abstract : Kramers–Kronig relations can be used to control the interplay of light absorption and dispersion. This concept is demonstrated by using bright commodity food dyes to design non-toxic high refractive index fluids. Abstract : For a number of optical applications, it is advantageous to precisely tune the refractive index of a liquid. Here, we harness a well-established concept in optics for this purpose. The Kramers–Kronig relation provides a physical connection between the spectral variation of the (real) refractive index and the absorption coefficient. In particular, a sharp spectral variation of the absorption coefficient gives rise to either an enhancement or reduction of the refractive index in the spectral vicinity of this variation. By using bright commodity dyes that fulfil this absorption requirement, we demonstrate the use of the Kramers–Kronig relation to predictively obtain refractive index values in water solutions that are otherwise only attained with toxic specialised liquids.